Antenatal vitamin D exposure and childhood eczema, food allergy, asthma and allergic rhinitis at 2 and 5 years of age in the atopic disease‐specific Cork BASELINE Birth Cohort Study. Issue 11 (29th August 2018) - Hennessy, Áine; Hourihane, Jonathan O'B; Malvisi, Lucio; Irvine, Alan D.; Kenny, Louise C.; Murray, Deirdre M.; Kiely, Mairead E.
Abstract: Background: Prospective studies of antenatal and infant vitamin D exposure and atopic disease from extensively characterised, disease‐specific, maternal‐infant cohorts with gold standard analysis of vitamin D status and clinically validated atopic outcomes are lacking. This study aimed to investigate associations between intrauterine vitamin D status and atopic outcomes in an extensively characterised, disease‐specific, maternal‐infant cohort. Methods: Circulating 25‐hydroxyvitamin D (25(OH)D) was measured in maternal sera at 15 weeks of gestation (n = 1537) and umbilical cord blood( n = 1050) using a CDC‐accredited LC‐MS/MS platform, and the association with clinically validated atopic disease outcomes (eczema, food allergy, asthma, allergic rhinitis) at 2 and 5 years was explored using multivariable logistic regression. Results: Persistent eczema in the first 2 years of life was present in 5% of infants. Food allergy at 2 years was confirmed in 4%. The prevalence of aeroallergen sensitisation at 2 years was 8%. Asthma at 5 years was reported in 15% and allergic rhinitis in 5% of 5‐year‐olds. There were no significant differences in the distributions of maternal 25(OH)D at 15 weeks of gestation (mean [SD] 58.4 [26.2] and 58.5 [26.1] nmol/L) and cord 25(OH)D concentrations (mean [SD] 35.2 [17.8] and 35.4 [18.3] nmol/L) between children with and without atopic disease. Neither maternal (aOR [95% CI]: 1.02 [0.97, 1.08], P = 0.450) nor cord 25(OH)D (aOR [95% CI]: 1.00 [0.91, 1.09], P = 0.991) were significant predictors of atopic disease outcomes in fully adjusted models. Conclusion: These data in a disease‐specific cohort with prospectively collected, validated atopic outcomes do not support an association between antenatal exposure to vitamin D and atopic disease outcomes in childhood.